Soil organic carbon depth profiles and centennial and millennial decay rates in tidal marsh, mangrove and seagrass blue carbon ecosystems - Nerea Piñeiro-Juncal; Miguel Ángel Mateo; Carmen Leiva-Dueñas; Eduard Serrano; Karina Inostroza; Montserrat Soler; Eugenia T. Apostolaki; Paul Lavery; Carlos M. Duarte; Anna Lafratta; Oscar Serrano (Communications Earth & Environment)
Abstract The management of coastal blue carbon ecosystems can contribute to mitigate anthropogenic greenhouse gas emissions. However, limited information on soil organic carbon (OC) decay rates in tidal marsh, mangrove, and seagrass soils hinders their inclusion in climate strategies and carbon-crediting schemes. Here, we analyzed downcore OC trends in 3761 soil cores from blue carbon ecosystems worldwide. A decrease in OC content with soil depth was measured in 63% of the cores, whereas stable and increasing trends were observed in 22% and 15% of the cores, respectively. Based on 85 profiles where OC decay could be modelled, the OC decay rate in blue carbon ecosystems was 0.023 ± 0.002 yr−1 over the last 100 years and 0.007 ± 0.0007 yr−1 over the last 1000 years. This results in the stabilization of 9% and 0.1% of the soil OC inputs 100 and 1000 yr after burial, respectively, showcasing the long residence time of OC in the sinks associated to blue carbon ecosystems. This study provides baseline estimates of soil OC decay under natural conditions for short- and long-term periods, and to assess the carbon abatement and additionally provided by carbon offsetting projects in blue carbon ecosystems.